2005
DOI: 10.2337/diabetes.54.5.1506
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic Acid Increases Lectin-Like Oxidized LDL Receptor-1 (LOX-1) Expression in Human Aortic Endothelial Cells

Abstract: Results from in vitro studies suggest that selected fatty acids, and especially linoleic acid (LA), can elicit endothelial dysfunction (ED). Because LA is increased in all LDL subfractions in patients with type 2 diabetes, this alteration may contribute to ED associated with diabetes. Lectin-like oxidized LDL receptor-1 (LOX-1) is the major endothelial receptor for oxidized LDL (oxLDL), and uptake of oxLDL through LOX-1 induces ED. To evaluate whether LA may contribute to the upregulation of endothelial LOX-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…Recently, we investigated the role of linoleic acid in the regulation of endothelial LOX-1, the molecular mechanisms involved in this effect and the role of LOX-1 in linoleic acidinduced oxLDL uptake by HAECs. Our results demonstrated that treatment of endothelial cells with linoleic acid, at concentrations similar to those found in diabetic patients [76], increases, in a timeand dose-dependent manner, endothelial LOX-1 [77]. This effect was inhibited by antioxidants and inhibitors of nicotinamide adenine dinucleotide phosphate (reduced form) (NADPH) oxidase, thus indicating a role of oxidative stress in linoleic acid-induced endothelial LOX-1 expression and identifying NADPH oxidase as one of the enzymatic superoxide sources activated by linoleic acid.…”
Section: Regulation Of Vascular Lox-1 In Diabetes-role Of Metabolic Fsupporting
confidence: 57%
See 1 more Smart Citation
“…Recently, we investigated the role of linoleic acid in the regulation of endothelial LOX-1, the molecular mechanisms involved in this effect and the role of LOX-1 in linoleic acidinduced oxLDL uptake by HAECs. Our results demonstrated that treatment of endothelial cells with linoleic acid, at concentrations similar to those found in diabetic patients [76], increases, in a timeand dose-dependent manner, endothelial LOX-1 [77]. This effect was inhibited by antioxidants and inhibitors of nicotinamide adenine dinucleotide phosphate (reduced form) (NADPH) oxidase, thus indicating a role of oxidative stress in linoleic acid-induced endothelial LOX-1 expression and identifying NADPH oxidase as one of the enzymatic superoxide sources activated by linoleic acid.…”
Section: Regulation Of Vascular Lox-1 In Diabetes-role Of Metabolic Fsupporting
confidence: 57%
“…Because LOX-1 is the major receptor for oxLDL expressed in endothelial cells, presumably mediating the majority of the uptake of oxLDL by these cells, induction of endothelial LOX-1 may represent a new mechanism by which fatty acids promote endothelial dysfunction. Our finding that up-regulation of LOX-1 by linoleic acid is associated with enhanced uptake of oxLDL uptake by endothelial cells supports this possibility [77]. Endothelial dysfunction can be described as impairment in the generation and function of NO.…”
Section: Regulation Of Vascular Lox-1 In Diabetes-role Of Metabolic Fsupporting
confidence: 57%
“…Finally, high levels of glucose were shown to enhance LOX-1 [3,25], although Chen et al [26] did not observe such an effect, but were unable to modify endothelial RAGE expression. By return, activation of these 2 receptors results in the intracellular enhancement in ROS formation [27][28][29], and to the activation of the above-mentioned redox transduction/ transcription pathways [25,17], thus contributing to the vicious circle of endothelial dysfunction in the diabetic state.…”
Section: Discussionmentioning
confidence: 99%
“…These unsaturated fatty acids can elicit endothelial dysfunction and are closely linked with atherogenesis. Maingrette et al found that linoleic acid enhanced, through LOX-1 activation, ox-LDL uptake by endothelial cells with involvement of NF-κB [67]. It is probable that linoleic acid is an important metabolic factor that participates in the development of diabetic atherosclerosis through activation of LOX-1/NF-κB pathway.…”
Section: Role Of Lox-1 In the Development Of Diabetic Cardiovascular mentioning
confidence: 95%